PENGELOLAAN SAMPAH DI KOTA SEMARANG UNTUK MENUJU KOTA BERSIH - Hariyanto, Hariyanto (Jurnal Geografi, 2014)
This study aimed to: 1) determine how much waste volume which resulted by theSemarang City residents, 2) determine waste management of Semarang City inorder to seize title âthe cleanest cityâ. The method used was descriptivequantitative. Population of this study was 70 families (household) which taken bypurposive random sampling. The results of this research showed that wastevolume resulted was 1000-1500 tonnes per day, with 8-12% increasement peryear. Waste volume was affected by the number of members from each household,economic level, and type of activity. 61.2% was organic waste and the rest wasnon-organic waste. The waste management conducted by transported to landfill(31%), burned or dumped (53%), disposed to river or sewer (15%), andcomposted (1.5%). The community considered that waste problem isgovernments business, not communityâs business. The waste managementapproach was focused to after waste produced and not been directed to decreasewaste volume before produced.